PATRIARCHY AND GENDER PERSPECTIVES - GLIMPSES FROM THE APPALACHIAN TRAIL - M. Rajalakshmi, Dr. N. Latha, (International Journal of Modern Agriculture, 2021)
Women today, are scaling great heights and achieve things unparalleled in their lives. From education to exploring the mysteries of space, women have no stone left unturned. In the same world where we live in there are petit worlds that have women who undergo torments, who toil for their survival, struggle keep up their culture codes and willingly bind themselves to shackles that the patriarchal society has created. One such culture that has always been looked with awe for their myths, taboos and cultural codes is the Appalachian society. Domestic violence is on high tide in Appalachia in this meta modern world. This article draws the individual and social status of women in Appalachia.